Interpersonal Relationships as a Key Factor In the Successful Implementation of Organizational Culture - Herman Yoseph; Siti Zulaikha; Supadi (South Sulawesi Education Development (SSED), 2025)
This research aims to examine the influence of interpersonal relationships on the implementation of organizational culture. Good interpersonal relationships are one of the keys to implementing organizational culture, one of which is in educational institutions. This research sample involved school principals and junior high school teachers in the Strada Association throughout the Special Region of Jakarta. The research method uses quantitative, data collection is carried out using a Likert scale. The data was then analyzed using Microsoft Excel, the analysis results revealed that the t-count value (5,007) exceeded the t-table value (2,365), leading to the rejection of the null hypothesis (Ho) and the acceptance of the alternative hypothesis (H1), indicating that the path coefficient was significant. These findings indicate that there is a real positive direct influence of interpersonal relationships on the implementation of organizational culture. Interpersonal relationships with autonomy support, competency support, and connectedness support make the implementation of organizational culture better. Support is not only provided by school leaders or management, teachers as colleagues or employees who support school administration. But parents do this as a form of support for connectedness so that the implementation of organizational culture runs well.